The Buying and Selling Behavior of Individual Investors at the Turn of the Year: Discussion - Ziemba, William T. (Journal of Finance, 1988)
William T. Ziemba, The Buying and Selling Behavior of Individual Investors at the Turn of the Year: Discussion, The Journal of Finance, Vol. 43, No. 3, Papers and Proceedings of the Forty-Seventh Annual Meeting of the American Finance Association, Chicago, Illinois, December 28-30, 1987 (Jul., 1988), pp. 717-719